Dietary methionine requirement for optimal growth performance and carcass characteristics in finishing gilts - Loughmiller, J.A.; Tokach, Michael D.; Titgemeyer, Evan C.; Bergstrom, J.R.; Kim, I.H.; Smith, J.W.II; Nessmith, W.B.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In Exp. 1, increasing dietary methionine from .12 to .22% (.10 to .20% apparent digestible methionine) in diets containing excess cystine had no effect on ADG, ADFI, 10th rib fat depth, and longissimus muscle area in finishing gilts from 130 to 190 lb. However, increasing dietary methionine tended to linearly improve feed efficiency. In Exp. 2, increasing dietary methionine from .11 to . 17% (. 10 to . 15% apparent digestible methionine) in diets containing excess cystine resulted in linear improvements in ADG, ADFI, and F/G in finishing gilts from 160 to 230 lb. Quadratic improvements were observed for F/G. No effect was seen on 10th rib fat depth. These data suggest that finishing gilts fed .58% total lysine (.50% apparent digestible lysine) require approximately .14% (3.3 g/d) total methionine or .125 %, (2.9 g/d) apparent digestible methionine.
Keywords: Swine; Growth; Methionine; Finishing pigs